(untitled) (Third Sector Social Economic Review, 2024)
Omnichannel service takes the customer experience in chain market retailing to a completely different dimension. The global pandemic period has had profound effects on channel management in chain markets, as in many sectors. The aim of the study is to examine the challenges, opportunities and strategies in omnichannel management in chain supermarket retailing. In accordance with this purpose, qualitative research method was preferred.In-depth interviews were conducted by asking twelve structured open-ended questions to a total of twelve participants ,who are working in chain supermarket retailing, including four senior and middle level managers from the companies. The interview questions were based on open-ended questions developed by Sousa (Sousa et al., 2021). The content was analyzed in the analysis of the qualitative data obtained in the research. analysis was used, themes were determined based on the relevant literature, codes were extracted and findings were presented with a content analysis suitable for qualitative research. Market growth, new consumer behaviors, digitalization, and integration of online and offline channels have been identified as opportunity areas. Moreover, the management of omnichannel strategies during the global Covid19 pandemic has been characterized by various challenges and successes. Factors such as stock management and inventory accuracy, labor shortage and delivery timing and quality are the main challenges that negatively affect operational efficiency and customer satisfaction. Improving logistics processes, gaining qualified workforce and achieving customer satisfaction targets are key to sustainable success in supermarket chain retailing market.